2019
DOI: 10.1111/jmwh.12990
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Management of Common Ailments in Women Who Are Breastfeeding

Abstract: According to the Centers for Disease Control and Prevention, the rate of breastfeeding in the United States has increased 34% between 2005 and 2015. Women who breastfeed can require treatment of various common illnesses. When caring for women who are breastfeeding, health care providers may unnecessarily discourage them from breastfeeding during treatment. Choosing the appropriate medications for these individuals is critical to ensure the woman is effectively treated, infant exposure to medication is minimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The articles in this issue that address pharmacologic management of common breastfeeding ailments by Dogruluk and care of women with primary breast engorgement by Gresh provide content for provider-oriented breastfeeding education. 10,11 While knowledge and education about breastfeeding can be helpful, breastfeeding support will be effective only if it is consistently offered. The pilot study in this issue published by Spisma et al collected data from women during their postpartum hospitalization and found that non-Hispanic white women are significantly more likely to room-in and less likely to be offered formula or pacifiers when compared to non-Hispanic black women.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The articles in this issue that address pharmacologic management of common breastfeeding ailments by Dogruluk and care of women with primary breast engorgement by Gresh provide content for provider-oriented breastfeeding education. 10,11 While knowledge and education about breastfeeding can be helpful, breastfeeding support will be effective only if it is consistently offered. The pilot study in this issue published by Spisma et al collected data from women during their postpartum hospitalization and found that non-Hispanic white women are significantly more likely to room-in and less likely to be offered formula or pacifiers when compared to non-Hispanic black women.…”
mentioning
confidence: 99%
“…This curriculum provides a template for one very concrete way midwives can improve breastfeeding counseling and support in their institutions. The articles in this issue that address pharmacologic management of common breastfeeding ailments by Dogruluk and care of women with primary breast engorgement by Gresh provide content for provider‐oriented breastfeeding education …”
mentioning
confidence: 99%